2017
DOI: 10.1111/cen.13337
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oxysterol pathway genes in oestrogen‐positive breast carcinomas

Abstract: The expression of a number of oxysterol pathway genes is significantly modulated by ER expression and associated with the clinical stage of patients. However, the expression of oxysterol pathway genes was not found to modify the prognosis of ER+ patients with breast carcinoma treated with endocrine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recent data have shown that major cholesterol metabolites, such as 27-hydroxycholesterol and 6-oxocholestan-3beta,5alpha-diol, display tumor-promoter properties 37 , 38 . Therefore, we further analyzed the expression of a curated list of 63 oxysterol pathway genes in mus musculus (Supplementary Data 5 ) known to be involved in the main oxysterol pathway, oxysterol metabolism, oxysterol pathway genes regulation and oxysterol transport 39 . We observed 47 (out of 63) dysregulated oxysterol pathway genes in dietary cholesterol-associated NASH-livers compared to non-cholesterol-associated steatosis-livers, as well as 33 dysregulated oxysterol pathway genes in cholesterol-associated NASH-HCCs compared to their adjacent non-tumor livers (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that major cholesterol metabolites, such as 27-hydroxycholesterol and 6-oxocholestan-3beta,5alpha-diol, display tumor-promoter properties 37 , 38 . Therefore, we further analyzed the expression of a curated list of 63 oxysterol pathway genes in mus musculus (Supplementary Data 5 ) known to be involved in the main oxysterol pathway, oxysterol metabolism, oxysterol pathway genes regulation and oxysterol transport 39 . We observed 47 (out of 63) dysregulated oxysterol pathway genes in dietary cholesterol-associated NASH-livers compared to non-cholesterol-associated steatosis-livers, as well as 33 dysregulated oxysterol pathway genes in cholesterol-associated NASH-HCCs compared to their adjacent non-tumor livers (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival (OS) was calculated as the time from surgery to death or the last follow‐up date. The logistics of sample collection, storage, and processing have been described elsewhere [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have therefore combined our existing somatic variation data from targeted DNA sequencing (DNA‐seq) of a panel of 113 oxysterol‐related genes (Table S1 , [ 15 ]) with respective mRNA expression data obtained by mRNA sequencing (mRNA‐seq) and with the complete miRNA transcriptome data obtained by microarrays, from the same BC patients. The genes and their roles in oxysterol signaling are summarized in our previous publications [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%